Interplay between various crystalline and hexatic-B phases in 75OBC liquid crystal: X-ray diffraction and calorimetry study. Issue 9 (14th July 2020) - Voronov, Vitaliy P.; Muratov, Andrey R.; Sulyanov, Sergey N.; Molodenskiy, Dmitry S.; Dorovatovskii, Pavel V.; Grebenev, Vadim V.; Ostrovskii, Boris I.
ABSTRACT: X-ray diffraction and high-resolution adiabatic calorimetry have been used to study the polymorphic behaviour of 75OBC liquid crystal. On heating of 75OBC from the room temperature, the crystal phase (Cr- I ) melts directly to smectic A (Sm- A ) and then to isotropic phase. On cooling from isotropic phase the 75OBC undergoes successive transitions to Sm- A, hexatic B (Hex- B ), crystalline (Cr- II ) phases, and next to another crystal phase – Cr- III . The latter two crystalline phases were shown to relax slowly to Cr- I phase, which is stable at low temperatures. X-ray data indicate that the Cr- II phase possesses orthorhombic lattice with herringbone in-plane order of the molecules (Cr- E ). The Cr- I and Cr- III phases belong to different low symmetry monoclinic lattices. Our results demonstrate a complex polymorphism of 75OBC compound: the thermodynamic pathway that involves monotropic Hex- B and orthorhombic Cr- E phases corresponds to a local thermodynamic minimum, while the other ones showing melting from the Cr- I to Sm- A phase belongs to the global minimum. The similar thermal behaviour was observed for other members of nmOBC homologous series, possessing a Sm- A – Hex- B – Cr- E phase sequence on cooling. The 75OBC polymorphic behaviour is discussed in terms of molecular packing and stability of Cr- E orthorhombic lattice that precedes the transition to the Hex- B phase. GRAPHICAL ABSTRACT: uf0001